Developing a Supplementary English Speaking Material Based on the Communicative Language Teaching Method - Maskurotin Fauziah; Saadaruddaroini; Khoirul Huda (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research is aimed to develop a supplementary English Speaking Material Based On Communicative Language Teaching for VIII Grade of MTs Putra Putri Lamongan. It concerns how to provide speaking material based on Communicative Language Teaching for English teaching and learning. The researcher used Educational Research and Development, and the procedures are (1) Need analysis. (2) Developing material. (3) Expert Validation. (4) product revision I (5) Try-out (6) product revision II (7) Final Product. The product is a supplementary English speaking material entitled 'Speak Up with Pronunciation.' The development consisted of six chapters: Opening Class, Pronunciation, My Problem Day, Let's Speak, Word Connection, and Show Accent Your Speaking